PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING DENGAN METODE PETA PIKIRAN (MIND MAPPING) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MEMPELAJARI EKONOMI KELAS X MIA 1 SMA N 5 SURAKARTA TAHUN PELAJARAN 2015/2016 - Trima Rahayu; Soetarno Joyoatmojo; Sri Wahyuni (Department of Economics Education, Universitas Sebelas Maret, 2018)
The research aims to improve students’ economic learning outcomes through Quantum Learning model by using Mind Mapping method of X MIA 1 in SMA N 5 Surakarta. This research used classroom action research method. There were 2 cycles in this research which each cycle consisted of planning, implementation, observation and refelction. The subject of the research was X MIA 1 students in SMA N 5 Surakarta which consists of 35 students. Data were collected by observation, interview, test and documentation. These data were analyzed with descriptive comparative technique and critical analysis.The result of this research showed that the implementation of Quantum learning model with Mind Mapping method can improve students’ economic learning outcomes of X MIA 1 in SMA N 5 Surakarta. The percentage of students’ passing the test was increasing to 48,56% from 37,14% in pre-cycle, 74,30 % in cycle 1 and 85,70 % in cycle 2. Moreover, the mean score of the test is also increasing to 14,9 %, from 65,51 % in pre-cycle, 78,1 % in cycle 1, and 80,41 % in cycle 2. The conclusion based on the research is that Quantum Learning model with Mind Mapping method can improve students’ economic learning outcomes of X MIA 1 in SMA N 5 Surakarta.